1994
DOI: 10.1007/bf00024237
|View full text |Cite
|
Sign up to set email alerts
|

Ecological consequences of food partitioning for the fish population structure in a eutrophic lake

Abstract: In the highly eutrophic lake, Frederiksborg Slotsso, the diet composition of the bream (Abramis brama L .) and roach (Rutilus rutilus L.) populations was examined during three periods with different food availability . The length range of bream and roach was 9-34 cm (TL) and 5-18 cm (TL), respectively . The relative food composition was examined for 2 cm and 1 cm length intervals of bream and roach, respectively. During all three periods, bream shifted from benthic cladocerans (Alona sp.) to zooplankton and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(29 reference statements)
0
9
0
5
Order By: Relevance
“…The length of juvenile roach corresponded to that backcalculated for Estonian small lakes (Eesti ja¨rved, 1968) and for Finnish lakes (Horppila & Nyberg, 1999) and its length frequency distributions was similar to that in the eutrophic lake Frederiksborg Slotssø (Michelsen et al, 1994). Age composition showed a similar scarceness of 2-to 3-year-aged roach both in the pelagic and littoral zones, being obviously catchable as a refugee in reeds (Herzig et al, 2002), the biotope not explored in lake Verevi.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The length of juvenile roach corresponded to that backcalculated for Estonian small lakes (Eesti ja¨rved, 1968) and for Finnish lakes (Horppila & Nyberg, 1999) and its length frequency distributions was similar to that in the eutrophic lake Frederiksborg Slotssø (Michelsen et al, 1994). Age composition showed a similar scarceness of 2-to 3-year-aged roach both in the pelagic and littoral zones, being obviously catchable as a refugee in reeds (Herzig et al, 2002), the biotope not explored in lake Verevi.…”
Section: Discussionmentioning
confidence: 81%
“…A similar composition of fish is characteristic of mesotrophic lakes in southern Finland (Olin et al, 2002). In highly eutrophic lakes, the proportion of other cyprinids and percids, such as bream, white bream (Blicca bjoerkna) and ruff, increased (Michelsen et al, 1994;Olin et al, 2002). During the past years L. Verevi, especially its epilimnion, has changed from hypertrophic to mesotrophic with oligotrophic features while bream and ruffe have disappeared by now.…”
Section: Discussionmentioning
confidence: 95%
“…While it might be expected that results would be similar in shallow reservoirs, in a relatively shallow eutrophic lake in Denmark (mean depth 3.1 m), roach fed mainly on zooplankton (Michelsen et al 1994). Zoobenthos were of minor importance and detritus appeared only in periods of low animal-food availability.…”
Section: Discussionmentioning
confidence: 89%
“…The ability of roach and bream to consume detritus is one of the characteristics that gives them a competitive advantage over species like perch under eutrophic conditions (Persson 1983) and makes it possible for cyprinids to maintain dense populations despite shortage of high-value invertebrate food (Michelsen et al 1994). Persson (1983) observed that during the whole ice-free period, detritus made up a high proportion of the stomach contents of 3-to 4-year-old roach in a Swedish lake.…”
Section: Discussionmentioning
confidence: 99%